Analisis Pembentukan Portofolio Optimal dan Evaluasi Kinerja Investasi Menggunakan Model Indeks Tunggal pada Saham Indeks LQ45 di Bursa Efek Indonesia - A.A. Sagung Istri Pramanaswari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Investing in stocks is an investment instrument with high potential returns, but carries a relatively high level of risk. Therefore, investors require a diversification strategy to obtain a combination of stocks that can provide optimal returns with minimal risk. This study aims to analyze optimal portfolio formation using the Single Index Model and evaluate the performance of portfolios formed from stocks included in the LQ45 index on the Indonesia Stock Exchange in 2025. This study uses a descriptive quantitative method with secondary data in the form of daily closing prices of LQ45 stocks, the Jakarta Composite Index (JCI), and the interest rate of Bank Indonesia Certificates during the period January–December 2025. The analysis is conducted through the calculation of stock returns, market returns, expected returns, beta, alpha, residual variance, Excess Return to Beta (ERB), Cut-Off Point (C*), fund proportion, portfolio return, portfolio risk, and performance evaluation using the Sharpe Ratio, Treynor Ratio, and Jensen Alpha methods. The research results show that of all the stocks included in the LQ45 index, seven stocks meet the criteria for optimal portfolio formation: BBCA, BBRI, BMRI, TLKM, ASII, ICBP, and UNTR. The largest proportion of investment was placed in banking sector stocks due to their relatively high ERB values. The optimal portfolio generated an expected return of 0.274% per day, with a portfolio risk of 0.000082 and a portfolio beta of 1.19. The evaluation results showed a Sharpe Ratio of 0.261, a Treynor Ratio of 0.00196, and a Jensen Alpha of 0.00163, indicating good portfolio performance. This research demonstrates that the Single Index Model is capable of generating efficient portfolios through diversification, thereby reducing the unsystematic risk of each stock.